Promotion and Implementation of Bioenergy for a Better Environment - Abdeen Mustafa Omer (Graduate Program of Syiah Kuala University, 2014)
Abstract - There is strong scientific evidence that the average temperature of the earth’s surface is rising and this may be attribute to increased concentration of carbon dioxide (CO2), and other greenhouse gases (GHGs) in the atmosphere as released by burning fossil fuels. One of the chief sources of greenhouse gases is burning of fossil fuels. Biogas from biomass appears to have potential as an alternative energy source, which is potentially rich in biomass resources. In the present paper, current literature is reviewed regarding the ecological, social, cultural and economic impacts of biogas technology. In this article an attempt has been made to give an overview of present and future use of biomass as an industrial feedstock for production of fuels, chemicals and other materials. However, to be truly competitive in an open market situation, higher value products are required.